2020
DOI: 10.3389/fonc.2020.01693
|View full text |Cite
|
Sign up to set email alerts
|

Efavirenz and Lopinavir/Ritonavir Alter Cell Cycle Regulation in Lung Cancer

Abstract: Highly active anti-retroviral treatment (HAART) is currently the most effective treatment for HIV/AIDS. Additionally, HIV positive patients receiving HAART have a better health-related quality of life (HRQoL). Cancers previously associated with HIV/AIDS also known as the AIDS defining cancers (ADCs), such as Kaposi's sarcoma and non-Hodgkin's lymphoma have been on the decline since the introduction of HAART. However, non-AIDS defining cancers (NADCs), in particular, lung cancers have been documented to be on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…While lopinavir-ritonavir treatment is a standard therapy in HIV patients, studies in the last decade have examined these drugs as a possible anti-cancer treatment ( Dalva-Aydemir et al, 2015 ; Kast et al, 2016 ; Okubo et al, 2019 ; Marima et al, 2020 ). Lopinavir and ritonavir induce apoptosis in glioma, lung cancer, and other tumor cell lines, likely by downregulating pro-survival factors such as AKT while increasing endoplasmic reticulum (ER) and mitochondrial stress ( Kast et al, 2016 ; Okubo et al, 2019 ; Marima et al, 2020 ). Lopinavir and ritonavir also demonstrate some cytotoxicity in in kidney proximal tubule cells, another target of aminoglycoside-induced damage ( Walker et al, 1990 ; Humes, 1999 ; Vidal et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…While lopinavir-ritonavir treatment is a standard therapy in HIV patients, studies in the last decade have examined these drugs as a possible anti-cancer treatment ( Dalva-Aydemir et al, 2015 ; Kast et al, 2016 ; Okubo et al, 2019 ; Marima et al, 2020 ). Lopinavir and ritonavir induce apoptosis in glioma, lung cancer, and other tumor cell lines, likely by downregulating pro-survival factors such as AKT while increasing endoplasmic reticulum (ER) and mitochondrial stress ( Kast et al, 2016 ; Okubo et al, 2019 ; Marima et al, 2020 ). Lopinavir and ritonavir also demonstrate some cytotoxicity in in kidney proximal tubule cells, another target of aminoglycoside-induced damage ( Walker et al, 1990 ; Humes, 1999 ; Vidal et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, this combination causes, in urological cancer cells, endoplasmic reticulum stress and increases the expression levels of AMP-activated protein kinase and tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) receptor [132]. In lung cancer cells, the same combination induces cell cycle arrest, downregulates cell viability, and induces apoptosis [133]. Additionally, as a single treatment Lopinavir and its generated Lopinavir nitric oxide derivative inhibit cell proliferation, cause morphological changes, and induce reactive oxygen species production and apoptosis in melanoma [134].…”
Section: Lopinavirmentioning
confidence: 99%
“…Ample evidence supports the repurposing of Efavirenz for cancer therapy. In vitro, Efavirenz inhibits the progression of different cancer types, including colorectal, pancreatic [152,153], lung cancer [133], as well as to Glioblastoma [152], and leukemia [154]. Interestingly, this drug is not only effective as a single treatment but is also shown to synergize the effect of radiation therapy [155].…”
Section: Efavirenzmentioning
confidence: 99%
“…This combination is being tested in the treatment of lung cancer. It was shown that Lopinavir and Ritonavir exposure causes cell cycle arrest, decreased cell viability, and apoptosis in lung cancer cells [115]. Efavirenz is another antiretroviral drug that downregulates the synthesis of viral DNA by binding the viral reverse transcriptase [116].…”
Section: Anti-retroviral Drugsmentioning
confidence: 99%